Preparation and characterization of CO2 plasma treated polypropylene grafting with soybean oil. Issue 5 (February 2019) - Yuan, Song; Li, Yi; Zhang, Qiong; Wen, Jun
Abstract: In this study, the adhesive properties of the CO2 plasma modified polypropylene (PP) surfaces have been investigated. The proportion of soybean oil would affect the grafting rate. The grafting rate increased with the increasing of the proportion of soybean oil. The grafting rate decreased when the proportion of soybean oil beyond 50%.